Using poetry in teaching Russian language in university of Baghdad / faculty of langu: Использование поэзии в процессе обучения русскому языку на кафедре русского языка факультета языков Багдадского университета (Journal of the College of Languages (JCL), 2019)
There are many methods of teaching foreign language to non-native speakers now therefore the discovery of new methods - which make students understand the language , vocabulary & saves them as soon as possible – becomes one of the most important duties of teachers and educators .The personal experience shows that the teaching of the Russian language through memorizing Russian poetry is one of the fastest ways to master the language and know its rules and also improve the ability of translating vocabulary and being not able to save the Russian words only , but to make it complete too. Poetry is an article or text which loves by people and enjoy reading it, therefore, using it to teach foreign language has a positive reaction on students. As we mentioned it helps greatly to absorb the language.A lot of professors and experts in teaching methods _ specialists in language teaching for foreign students in different grades _ use poetic texts in teaching a foreign language to avoid the boredom in teaching grammar and make it interesting. АннотацияСтатья посвящена возможности использования в обучении русскому языку как иностранному Есть много методов обучения иностранному языку для не-носителей языка в настоящее время до открытия новых методов-которые делают студенты понимают язык, словарный запас и сохраняет их как можно скорее-становится одним из самых важных обязанностей учителей и преподавателей . Личный опыт показывает , что преподавание русского языка через поэзию русского языка является одним из самых быстрых способов овладеть языком и знать его правила, а также улучшить способность переводить словарный запас и быть не в состоянии сохранить только русские слова, но и сделать его полным.